Study on the Applicability of Isomaltulose (Palatinose) in Beer and Beer Specialties, and its remarkable Results - Pahl, R.; Methner, F.-J.; Schneider, J.; Kowalczyk, J.; Hausmanns, S.; Radowski, A. (BrewingScience, 2008)
The functional disaccharide isomaltulose (Palatinose) was tested to determine its suitability as an ingredient in beer and beer specialties, and its potential fermentability by typical beer contaminants, and typical beer production yeasts. It was shown that all tested beer contaminants were in the majority of the cases completely unable to ferment isomaltulose. The same was true for most of the tested brewing yeasts. As a result of the non-fermentability, promising results were obtained with respect to the microbiological stability, and to the sensorial profile and taste of beer and beer specialties.